Gender and Diversity in a Problem and Project Based Learning Environment: A Book Review (Asean Journal of Engineering Education, 2023)
"Gender and Diversity in a Problem and Project Based Learning Environment" by Xiangyun Du is a pioneering exploration of the intersection between pedagogical innovation and gender diversity in engineering education. This book expertly navigates the challenges of achieving gender inclusivity in male-dominated disciplines while showcasing the transformative potential of Problem-Based Learning (PBL) methodologies. Through insightful case studies, critical analyses, and a rich synthesis of research findings, Du presents a compelling argument for the effectiveness of PBL as a catalyst for fostering diversity and equity in engineering education. Her work not only informs but also inspires positive change, making it an indispensable resource for educators, researchers, and policymakers striving to create more inclusive and equitable engineering education.
Keywords: diversity; gender equality; inclusivity; pedagogy; women empowerment